VISUALISASI RANGKIANG DALAM PENCIPTAAN SELENDANG DENGAN TEKNIK BATIK DAN SULAMAN - Sherly, Safira; Yeni, Yeni (Institut Seni Indonesia Padangpanjang, 2023)
The purpose of creating this artwork is to visualize rangkiang with Minangkabau motifs on shawls using batik and embroidery techniques. The method used in making this shawl goes through the stages of preparation, elaboration, synthesis, concept realization and completion. The results achieved in the creation of this embroidery work are the shawls entitled motif rangkiang jo motif itiak pulang patang, motif rangkiang jo motif aka cino, motif rangkiang jo motif rantiang babungo, motif rangkiang jo motif kaluak paku, motif rangkiang jo motif siriah gadang, motif rangkiang jo motif padi, motif rangkiang jo motif rantiang babungo.Adanya tujuan penciptaan karya seni ini adalah untuk memvisualkan rangkiang dengan motif Minangkabau pada kain selendang dengan teknik batik dan sulam. Metode yang digunakan dalam penciptaan selendang ini melalui tahap persiapan, elaborasi, sintesis, realisasi konsep dan penyelesaian. Hasil yang dicapai dalam penciptaan karya seni sulaman ini yaitu berjudul motif rangkiang jo motif itiak pulang patang, motif rangkiang jo motif aka cino, motif rangkiang jo motif rantiang babungo, motif rangkiang jo motif kaluak paku, motif rangkiang jo motif siriah gadang, motif rangkiang jo motif padi, motif rangkiang jo motif rantiang babungo.